Pengaruh Inflasi terhadap Tingkat Kriminalitas di Sumatera Utara - Rebecca Putri Sihaloho; Rojelita Catrina Simarmata; Riska Zunaida Sikumbang; Indah Safitri Manurung; M. Irfandi Syahputra; M. Rayhan Satria (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The objective of this study is to investigate the correlation between inflation and crime rates in North Sumatra and assess the impact of inflation on crime. The search utilizes secondary data collected from 2016 to 2020, obtained from BPS. The primary analytical method used is linear regression. The study results indicate that there is no statistically significant association between the inflation rate and the crime rate in North Sumatra. Despite the modest correlation coefficient between the two variables, the ANOVA analysis indicates that the entire regression model lacks statistical significance. The regression coefficient for the inflation variable is likewise non-significant, suggesting that inflation does not have a substantial influence on the crime rate in the region.